Upaya Meningkatkan Hasil Belajar Siswa Pada Materi Bioteknologi Dan Produksi Pangan Melalui Penerapan Model Pembelajaran Discovery Learning Di Kelas IX.1 SMP Negeri 1 Blangkejeren Tahun Pelajaran 2020/2021 - Aisyah (Journal of Technology and Literacy in Education, 2022)
This study aims to improve student learning outcomes in biotechnology and food production materials through the application of the discovery learning model in class IX.1 of SMP Negeri 1 Blangkejeren for the 2020/2021 school year. This research was conducted in a place where the researcher taught, namely at SMP Negeri 1 Blangkejeren in the even semester of the 2020/2021 school year carried out for 3 months starting from January to March 2021. The subject of this research was IX.1 SMP Negeri 1 Blangkejeren in the 2021 academic year. /2021, totaling 29 students. This research is classroom action research for two cycles, each cycle consists of planning, action, observation and reflection stages. Data collection techniques in this study are cycle tests and observations of teacher and student activities. Data analysis techniques in this study were analyzed descriptively qualitatively. The results showed that student learning outcomes in the first cycle of 29 students, obtained the percentage value of completeness of 62.07% or as many as 18 students who had reached the KKM with a classical average of 81.55. While in the second cycle the percentage of completeness increased to 89.66% or as many as 26 students who had reached the KKM increased by 24.59%. With the classical average in the second cycle of 90, an increase of 8.45. The researcher’s activities in carrying out the learning process using the discovery learning learning model were carried out by researchers in the first cycle the overall average obtained was 3.52 in the good category, while in the second cycle the overall average obtained was 4.5 in the very category. good, and an increase of 0.98 from the first cycle. Student activity in following the learning process the average value of the percentage in the first cycle of 69.75% was in the good category. While in the second cycle the average percentage is 90.5%, is in the very good category and has an increase of 20.75%. So it can be concluded that through the application of discovery learning learning models can improve student learning outcomes in biotechnology and food production materials in class IX.1 of SMP Negeri 1 Blangkejeren for the 2020/2021 school year.